Stochastic Analysis of a Non Uniform Surface of Bridges - Zouaoui, Samia; Kadri, Tahar (Ingeniería Investigación y Tecnología, 2013)
The study of the problem of effects of surface roughness in bridges has been a topic of interest for over a century. For the treatment of this problem, multiple longitudinal profiles of pavements during different periods of life of bridges could be addressed. First, the construction period, the profile is linked to anomalies due to design errors and embodiments, other anomalies are due to vibrations parasitic. For the 2nd period, we study two profiles, one that reflects the state of the slab or platform of the bridge just after it was in service and for the 2nd profile after a certain time, which can range up to 15 years. In this context, we propose a stochastic analysis to fully understand the behavior of a structure in service while including a set of parameters often not considered in the normative evaluation procedures.